2013
DOI: 10.1007/s11046-013-9641-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Oral Histoplasmosis Presenting as Fever of Unknown Origin in a Portuguese Hemodialysis Patient

Abstract: The authors report a clinical case of an isolated oral histoplasmosis in a hemodialysis patient that presented with fever of unknown origin and had an unremarkable physical examination. During the investigation, a Gallium scan showed uptake in the oral cavity and soon after the oral cavity examination revealed a granulomatous lesion on the tooth 26. Histopathologic findings were compatible with histoplasmosis. The treatment regimen included liposomal amphotericin B followed by itraconazole consolidation therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…We confirmed that the latency period from the last time spent in an endemic area to the time of diagnosis can be extremely long, except in the case of travellers with acute pulmonary histoplasmosis: median latency is 66 months among PLWH, 6 years among immunocompetent expatriates/migrants, and between as short as 3 weeks [83] and as long as 42 years [78] among patients with OIC. As previously shown by epidemiological studies of endemic areas [152] and among travellers [8], a majority of our cases involved males (440/659 66.8%) [12,, although the male-to-female ratio was lower (2:1) than that observed in other studies (4:1) [152].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We confirmed that the latency period from the last time spent in an endemic area to the time of diagnosis can be extremely long, except in the case of travellers with acute pulmonary histoplasmosis: median latency is 66 months among PLWH, 6 years among immunocompetent expatriates/migrants, and between as short as 3 weeks [83] and as long as 42 years [78] among patients with OIC. As previously shown by epidemiological studies of endemic areas [152] and among travellers [8], a majority of our cases involved males (440/659 66.8%) [12,, although the male-to-female ratio was lower (2:1) than that observed in other studies (4:1) [152].…”
Section: Discussionsupporting
confidence: 76%
“…The countries reporting the most cases were France (8, 28.6%), Spain (6, 21.4%), and The Netherlands (5, 17.8%). Sixteen patients had progressive disseminated histoplasmosis (57.1%), which was revealed by a picture of haemophagocytic lymphohistiocytosis (HLH) in five cases [76,83,84,88,92]; two had intestinal histoplasmosis [89,91], one of whom was initially misdiagnosed as having Crohn's disease leading to HLH following treatment with infliximab [91]; the remaining ten had apparently localised disease with cerebral involvement [72], endocarditis [77], pyomyositis [63], or pulmonary [87], oral [78], laryngeal [80], liver [44], osteoarticular [89] or skin diseases [39]. Seven cases (25%) were characterised by ulcerated lips or the involvement of the oropharyngeal mucosa [70][71][72]74,81,84,88].…”
Section: Patients With Other Immunocompromising Conditions (Oic)mentioning
confidence: 99%
“…There are several cases worldwide reported with oral histoplasmosis in immunocompetent patients [7], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19]. In Portugal, only one case was published about an oral histoplasmosis in a hemodialysis patient with persisted fever [9].…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal, only one case was published about an oral histoplasmosis in a hemodialysis patient with persisted fever [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation